COMPARATIVE STUDY BETWEEN THE BROAD GUIDELINES OF STATE POLICY AND THE MEDIUMâ€TERM DEVELOPMENT PLAN - Anwar, Syaiful (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
The Broad Guidelines of State Policy (BGSP) or Garis-Garis Besar Haluan Negara (GBHN) and the National Medium-Term Development Plan (NMDP) or Rencana Pembangunan Jangka Menengah Nasional (RPJMN) are important state policies in the execution of Indonesia's national development in various aspects of the life of the nation and state. The BGSP is no longer exists, and the MDP is still in effect today. The purpose of this study is to compare the two policies to obtain the superiorities and weaknesses of each when faced with several parameters obtained from various theories related to politics and law. This study is qualitative research using comparative studies in its analysis. From this study, it was found that in general, the BGSP made by the People's Consultative Assembly (PCA) or Majelis Permusyawaratan Rakyat (MPR) had a greater relative superiority when compared to the MDP made by the Government of the Republic of Indonesia.